Komposit Hybride Serat Buah Kelapa dan Tebu Pada Bagian Akar, Batang, Pucuk Bermatrix Polyester BQTN 157 - Subhan, Muhamad; Ergiantoro, Anugerah; Yuliyanto, Yuliyanto (Manutech : Jurnal Teknologi Manufaktur, 2023)
The buildup of sugarcane bagasse fiber and coconut pulp fiber will cause rotting and an unpleasant odor, therefore it needs to be handled seriously. One of them is making natural fiber composites. The aim of the research was to obtain the highest tensile test value for a hybrid composite of coconut fiber and sugarcane fiber in the roots, stems and shoots with a volume fraction of 10% sugarcane fiber - 20% coconut fiber, 20% sugarcane fiber - 10% coconut fiber and sugarcane fiber. 15% - Coconut Fiber 15%, with 5% NaOH alkaline treatment for 2 hours. Samples were made using the hand lay-up method. The analysis was carried out using the direct experimental design method. The result was the highest tensile strength of 17.2 Mpa at a volume fraction of 10% Sugarcane Fiber - 20% Coconut Fiber and there was a decrease in tensile strength at a volume fraction of 20% Sugarcane Fiber - 10% Coconut Fiber. The lowest tensile strength is at a volume fraction of 20% Sugarcane Fiber - 10% Coconut Fiber with a tensile test strength value of 6.6 Mpa, meaning that the more fiber distribution in the resin in each composite will strengthen the bond between the matrix and fiber which causes the composite to be strong and not brittle. . In the micro photo, soaking in 5% NaOH for 2 hours was not able to clean the dirt or film attached to the coconut fiber, whereas in sugar cane fiber, soaking for 2 hours was able to clean the layer or dirt on the fiber. Dirt that sticks to it will affect the bond between the fiber and resin.